The lake on fire - Brown, Rosellen (Sarabande Books, 2018)
"After more than a decade, Rosellen Brown, author of ten celebrated books, is back with a gritty, absorbing, and deeply felt novel. The Lake on Fire is an epic narrative that begins among immigrants on a failing Wisconsin farm. Chaya and her strange, brilliant, little brother Asher depart for Chicago only to discover that the Gilded Age is as empty a façade as the beautiful Columbian Exposition attracting thousands to Lake Michigan's shore. They scrape together a meager living--she in a cigar factory; he, roaming the city and stealing books and jewelry to share with the poor, until they find different paths of escape. Chaya's becomes a deeply conflicted love story and Asher, haunted by his loyalty to the Fair's abandoned workers, is responsible for an astonishing terrorist act. The abandoned Fair burns to the ground as the city goes on with its usual business in this profound narrative that resonates eerily with today's news"--